Risks, Experience, Ease of Purchase Terhadap Purchase Intention Makanan Sehat dengan Moderator Fear Of COVID-19 - Raihan Muslim Fajri Said; Citra Kusuma Dewi (Jurnal Manajemen, 2022)
This research is motivated by the COVID-19 pandemic, that has made Indonesians pay more attention to their health so they don't get infected with the virus. Efforts are made by consuming healthy foods. The increasing consumption of healthy food causes various kinds of problems ranging from risks that consumers must bear, unpleasant shopping experiences, to obstacles for consumers when obtaining healthy food. The purpose of this study was to examine the effect of Overall risk, Purchase experience, and Ease of purchase on Purchase intention, as well as examine how high the Moderation of Fear of COVID-19 is on the relationship between Ease of purchase and Purchase intention of Healthy Food. This type of research is included in quantitative and causal. The analysis used is descriptive analysis usingStructural Equation Model-Partial Least Square (SEM-PLS). Technique. The sampling used is non-probability sampling with purposive sampling type. Then the number of samples in this study were 385 respondents in the Jabodetabek and Bandung City communities who had consumed healthy food. The results of this research using SEM-PLS are all independent variables consisting of Overall risk, Purchase experience, and Ease of purchase have a positive and significant influence on the dependent variable, namely Purchase intention. In addition, the moderator of the Fear of COVID-19 study did not moderate the relationship between Ease of purchase and Purchase intention. Keywords : Overall risk, Purchase experience, Ease of purchase, Purchase intention, Fear of COVID-19 Keyword: Risk; Experience; Ease; Intention; COVID-19